Influence of evolutionary theory on the development of zoogeographical studies of Ukrainian scientists - Rohozha, M. M. (History of science and technology, 2014)
<span title="Вихід у світ праці Ч. Дарвіна «Походження видів шляхом природного добору або виживання найбільш пристосованих у боротьбі за життя» (1859) сповістив світ про набуття права на громадянство нової наукової ідеї.">The publication of the work of Charles Darwin "The Origin of Species through Natural Selection or Survival of the Most Suited in the Struggle for Life" (1859) informed the world about the acquisition of the right to citizenship of a new scientific idea. <span title="Усвідомлення того, що британський вчений Ч. Дарвін створив еволюційну теорію у природничонауковому розумінні, а потім наступне поступове завоювання нею все більшого кола прихильників у наукових колах та поза ними стало доконаним фактом.">The realization that the British scientist C. Darwin created an evolutionary theory in the natural sciences, and then the subsequent gradual conquest of it by an increasing number of adherents in the scientific circles and beyond them became a feasible fact. Over time, the theory of evolution turned into a powerful engine of knowledge of the surrounding world, became the methodological and epistemological basis of such a process. Due to this, the development of biological sciences has acquired new qualities, since relied on substantiated statements (postulates), that is, material laws. <span title="Розвиток біологічних досліджень у Південно-Західному краї Російської імперії, згодом СРСР, а потім в Україні, природно, проходив у контексті поступального розвитку світової природознавчої науки, з усіма загальними особливостями та специфічними вітчизняними привнесеннями, властивими кожній суспільно-політичній формації у її розвитку.">The development of biological research in the Southwest Territory of the Russian Empire, subsequently the USSR, and then in Ukraine, naturally, took place in the context of the steady development of world science science, with all the general features and specific domestic influences inherent in each socio-political formation in its development. Formation of the research space in the field of domestic zoological science, in our opinion, was distinguished by several peculiarities. <span title="Вони стосувалися послідовних етапів формування території України в її сучасному вигляді, наукових шкіл та визначення пріоритетів у напрямах досліджень, етапів ведення таких робіт та, головне, науково-світоглядних позицій науковців-природодослідників.">They concerned the successive stages of the formation of the territory of Ukraine in its modern form, scientific schools and the definition of priorities in the areas of research, stages of conducting such works and, most importantly, the scientific and philosophical views of scientists-naturalists. <span title="Саме питання формування науково-світоглядних уявлень українських зоогеографів під впливом еволюційної теорії Ч. Дарвіна та їх вплив на зміст і характер зоогеографічних досліджень в Україні й стали предметом розгляду пропонованої статті.">It is the question of the formation of scientific and worldview views of Ukrainian zoogeographers under the influence of Darwin’s evolutionary theory and their influence on the content and nature of zoogeographical research in Ukraine and became the subject of consideration of the proposed article.